Aspecte privind structura maritală a populației Republicii Moldova în baza datelor studiului Generații și Gen (2020) - Chistruga-Sînchevici, Inga (Calitatea Vieții, 2022)
The population of the Republic of Moldova has adopted some trends recorded in European countries regarding matrimonial behavior and attitudes: postponing the official registration of marriage to a more mature age, the spread of premarital cohabitation, and celibacy for good. At the same time, the population has a favorable attitude towards marriage, and the need to create a family seems to be dominant in the socio-cultural context of the Republic of Moldova. The article highlights the transformations occurring in the marital behavior of the population of the Republic of Moldova and is based on the data of the Generations and Gender (GGS) study, carried out in 2020 by UNFPA Moldova. The results of the analysis of both empirical data and official statistics reflect the same changes in the evolution of marriage and divorce phenomena. The research on the aspects related to the partner’s presence, marriage, the average age at marriage, the average number of partnerships, and involvement in cohabitation shows a series of different characteristics for men and women depending on age. Cohabitation, as a marital trend in the Republic of Moldova, is practiced more and more, most often turning into marriage. Nuptial behavior is far from the stage where there is no distinction between cohabitation and marriage. The study found that the stability of marital relationships is influenced by a series of socio-demographic and economic factors: the presence of children, the duration of the relationship, the environment of residence, etc.